Connecting the Dots: Heart Failure and Insomnia - Marcin Kapica; Karol Momot; Aleksandra Żmijewska; Mateus Sztybór; Maria Krzyżanowska; Monika Maleszewska; Julia Piątkiewicz; Gabriela Nowak; Mikołaj Wojtas; Karen Głogowska (Kazimierz Wielki University, 2024)
Introduction and aim. This study investigates the relationship between heart failure (HF) and insomnia, focusing on this two-way association's clinical significance, epidemiology, and management. Material and methods. Literature available in November 2023 was searched using Pubmed, Medline, Google Scholar, and Europe PMC with keywords associated with Heart Failure, Insomnia, and related pharmaceuticals. 69 articles were included. Analysis of the literature. Insomnia is associated with higher mortality and a potential risk of sudden cardiac death, particularly in individuals with HF. Treatment is challenging and side effects can worsen the symptoms of HF. The use of benzodiazepines in HF patients raises concerns about cardiovascular risks, prompting the exploration of other medications like nonbenzodiazepines, antidepressants with sedative effects, and histamine receptor antagonists. On the other hand, HF is also a condition that affects sleep quality. Drugs including ACE-I, beta-blockers, MRA, and SGLT2i are essential for its treatment. Some of them may have an impact on the intensity of insomnia. Conclusion. Considering the impact of insomnia medications on heart failure outcomes and vice versa is necessary. It is important to consider all aspects when treating these two conditions simultaneously.